INFORMATIZATION OF PROCESS TRAINING FOR SOFTWARE E - M. Luts`kiy; N. Sidorov (Kherson State University, 2010)
Process of the informatization by training for software is the key of improvement not only efficiency but also the quality of training, because the environment of the future activities is the information specialists. The implementation in the initial process of institutional, technological and technical means of information to create additional conditions for quality, professional training are considered.